Eksplorasi Kulit Sisa Industri Untuk Elemen Interior - Stephano Khristoforus Winarto; Yusita Kusumarini; Filipus Priyo Suprobo (Intra, 2019)
Leather has been used by human since ancient times. Its size and shape are depend on the animal. This differences in shape and size produce a lot of waste. This waste, by the industries that produced it are being thrown away because they did not have time to re-use it. This research aim to look for potential in leather waste from industries for interior element so the waste did not thrown away but get re-used to make a new product. By doing some experiment with leather waste using various techniques it can be concluded that leather waste has potential for interior element if treated correctly and with the right technique.